Synthesis, Characterization, Optical and Gamma Shielding Properties of La2O3 Doped Recycled PS-PVC/PCL Ternary Blend Composites - Oner, Ecem Ozen; Tatar, Cengiz; Kok, Mediha (Springer, 2025)
The oxide compound of lanthanum (La2O3), one of the rare earth elements, is one of the attractive materials with its p-type semiconductor properties and its radiation protection feature due to its high atomic number. In this study, smart composites were produced by doping La2O3 into a ternary blend of polycaprolactone (PCL), known as a smart polymer, with high-consumption polystyrene and polyvinyl chloride wastes and it was aimed to investigate the use of the produced composites as waste utilization, electronic applications and radiation shielding materials. For this purpose, composites with different La2O3 contents were produced by solution method. The change in the crystal structure of the produced polymeric composites was determined by XRD (x-ray diffraction) measurements and it was determined that the crystal properties of the polymeric composite increased with increasing La2O3 content. As a result of the analysis of the thermal properties of the composites, it was determined that the mass loss in the polymeric blend caused extra mass loss with the addition of La2O3 and the remaining mass loss increased. Evaluation of the Ultraviolet (UV) measurements of the produced composites revealed that the band energy value decreased from 4.02 eV to 3.89 eV. It was found to provide better results than polymeric composites with several high atomic number oxides when the results of gamma radiation shielding property measurements were analyzed.
Keywords: Recycled polymer; Composite; Optical property; Gamma shielding property; Rare earth oxide